2019
DOI: 10.1177/0886260519877950
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Dark Triad Personality Traits on the Relationship Between Parental Emotional Warmth and Aggression

Abstract: Previous research has indicated that positive parenting practices, such as parental emotional warmth, are associated with less negative outcomes in children. These negative outcomes can present during adolescence and during emerging adulthood. One negative consequence can be aggression, a problematic outcome with its own myriad consequences. The current study aimed to examine the effect of parental emotional warmth on adolescent and young adult aggression and the mediating effect of Dark Triad personality trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In the next step, we analyzed the interplay between parental behavior, Dark Triad traits and propensity for violence. In line with a recent study in 530 Chinese students [ 41 ], our results point towards a significant role of the manifestation of the dark traits in the association between parental rearing and violence. Interestingly, the effects regarding maternal parenting behaviour are stronger overall than the effects regarding paternal parenting behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…In the next step, we analyzed the interplay between parental behavior, Dark Triad traits and propensity for violence. In line with a recent study in 530 Chinese students [ 41 ], our results point towards a significant role of the manifestation of the dark traits in the association between parental rearing and violence. Interestingly, the effects regarding maternal parenting behaviour are stronger overall than the effects regarding paternal parenting behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…Malevolent creativity requires deliberate, innovative, and secretive harm, so Machiavellianism may be closer to malevolent creativity. As dark and callous personality traits, psychopathy is associated with dysfunctional impulsivity, including poor self-control, various cognitive deficits, and more risk-taking, so psychopathy is closer to aggression (see Liu et al, 2019) than malevolent creativity. The "callousness" of narcissism is more about self-centeredness and is further correlated with functional impulsivity that involves venturesome social engagement, so narcissism may have a moderate correlation with malevolent creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a reverse model was tested to assess whether the Dark Triad had an effect on malevolent creativity through perceived childhood neglect and found that childhood neglect only significantly mediated the relationship between psychopathy and malevolent creativity. Furthermore, since the Dark Triad mediating model has greater theoretical and empirical support than the reverse model (Jonason et al, 2014;Csathó and Birkás, 2018;Liu et al, 2019), the hypothesized model was regarded as the preferable of the two in describing relationships among the variables. Childhood neglect significantly positively predicted Machiavellianism (β = 0.28, p < 0.001), psychopathy (β = 0.36, p < 0.001), and narcissism (β = 0.20, p < 0.001).…”
Section: Structural Modelmentioning
confidence: 99%
“…In the DFPM, RFP, and AFP co-exist within an individual, influencing the development of personality (Bedford and Yeh, 2019). RFP, originated from secure attachment style in parent-child bonds, adequate parental care, and appropriate discipline, can prevent children from manipulating others (Machiavellianism), being self-centered (Narcissism), and acting in the absence of guilt (Psychopathy, see Jonason et al, 2014;Liu et al, 2019). According to life history theory, negative early life experiences, such as harsh parenting and unpredictable parental behavior, may result in pathological personality development (e.g., exploitation, manipulation; Csathó and Birkás, 2018).…”
Section: The Dark Triad As Mediatorsmentioning
confidence: 99%